Komunikasi Pentahelix dan Relasi Stakeholder dalam Pengelolaan Ekowisata Berbasis Masyarakat Berkelanjutan - Poppy Alicyana; Mariana Rista Ananda Siregar; Muhammad Reza (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
Sustainable community-based tourism management at the rural level often faces major challenges in coordinating different parties. This study analyzes the communication dynamics and stakeholder relationships in Ciwaluh Village's tourism management in Bogor Regency. This research employs a descriptive qualitative method to identify destination components through Buhalis' 6A framework (attraction, amenities, ancillary services, activity, accessibility, and available package) and maps actors using the Pentahelix approach and Stakeholder Relations theory. The findings indicate that Ciwaluh Village fulfills five of the six tourism components, with activity and available packages emerging as primary strengths rooted in ecotourism potential. A key finding reveals that the Tourism Awareness Group (Pokdarwis) functions not merely as a technical manager but has transformed into a strategic communication hub bridging Pentahelix actors. In stakeholder mapping, the Pokdarwis is identified as a definitive stakeholder with strong power, legitimacy, and urgency, while the media is identified as a discretionary stakeholder. The study emphasizes that local communities' communication autonomy is crucial for achieving synergy in sustainable community-based tourism.